Hearing threshold shifts among military pilots of the Israeli Air Force. Issue 1 (6th September 2017) - Kampel-Furman, Liyona; Joachims, Z; Bar-Cohen, H; Grossman, A; Frenkel-Nir, Y; Shapira, Y; Alon, E; Carmon, E; Gordon, B
Abstract : Background: Military aviators are potentially at risk for developing noise-induced hearing loss. Whether ambient aircraft noise exposure causes hearing deficit beyond the changes attributed to natural ageing is debated. The aim of this research was to assess changes in hearing thresholds of Israeli Air Force (IAF) pilots over 20 years of military service and identify potential risk factors for hearing loss. Methods: A retrospective cohort analysis was conducted of pure-tone air conduction audiograms of pilots, from their recruitment at 18 years of age until the last documented medical check-up. Mean hearing thresholds were analysed in relation to age, total flight hours and aircraft platform. Comparisons were made to the hearing thresholds of air traffic controllers (ATCs) who were not exposed to the noise generated by aircraft while on duty. Results: One hundred and sixty-three pilots were included, with flying platforms ranging from fighter jets (n=54), combat helicopters (n=27), transport helicopters (n=52) and transport aircraft (n=30). These were compared with the results from 17 ATCs. A marked notch in the frequency range of 4–6 kHz was demonstrated in the mean audiograms of all platforms pilots, progressing with ageing. Hearing threshold shifts in relation to measurements at recruitment were first noted at the age of 30 years, particularly at 4 kHz (mean shift of 2.97 dB, p=0.001). There was no statistical association between flying variables and hearing thresholds adjusted for age by logistic regression analysis. Conclusions: The audiometric profile of IAF pilots has a pattern compatible with noise exposure, as reflected by characteristic noise notch. However, no flight variable was associated with deterioration of hearing thresholds, and no significant difference from non-flying controls (ATCs) was seen.